POSSIBILITIES OF COMBINATIONAL MAGNESIAL AND NEUROPROTECTOR THERAPY IN PATIENTS WITH EARLY CEREBROVASCULAR PATHOLOGY - E.I. Gusev; O.A. Gromova; A.A. Nikonov; E.V. Uvarova; T.R. Grishina; L.E. Fedotova; O.A. Limanova; A.Yu. Volkov (Union of pediatricians of Russia, 2007)
The serum level of magnesium was evaluated in 232 teenagers and adolescents with early cerebrovascular diseases aged 16-21 years. In cases of magnesium deficiency, monotherapy with complex magnesium medication is an effective treatment both for concurrent magnesium deficiency and for early forms of cerebrovascular pathology with different patterns of vascular response (hyper_ and hypoconstrictive variants). Maximum normotensive effect of the therapy and maximal efficacy in treating vertigo and headaches is reached in combinational therapy with vinpocetin and complex magnesium medication. a combination of complex magnesium medication with bylobil potentiates antiasthenic effect, mostly through diminishing excessive neuron muscular irritability and paresthesiae.Key words: teenagers, magnesium, b6 vitamin, cavinton, bylobil, potentiative therapy, early forms of cerebrovascular diseases.